2020
DOI: 10.1002/1878-0261.12620
|View full text |Cite
|
Sign up to set email alerts
|

A 10‐year prediagnostic follow‐up study shows that serum RNA signals are highly dynamic in lung carcinogenesis

Abstract: The majority of lung cancer (LC) patients are diagnosed at a late stage, and survival is poor. Circulating RNA molecules are known to have a role in cancer; however, their involvement before diagnosis remains an open question. In this study, we investigated circulating RNA dynamics in prediagnostic LC samples, focusing on smokers, to identify if and when diseaserelated signals can be detected in serum. We sequenced small RNAs in 542 serum LC samples donated up to 10 years before diagnosis and 519 matched cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 59 publications
2
21
2
1
Order By: Relevance
“…Although previous studies have identified TGCT specific RNA profiles in patients ( 28 30 ), this has not been described for the pre-diagnostic period, as seen in our study. In contrast to our findings, highly dynamic pre-diagnostic RNA signals have been observed in lung cancer and breast cancer samples ( 27 , 47 , 48 ). The reason for this contrast may partly be due to the localization of the tumor within the testis.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although previous studies have identified TGCT specific RNA profiles in patients ( 28 30 ), this has not been described for the pre-diagnostic period, as seen in our study. In contrast to our findings, highly dynamic pre-diagnostic RNA signals have been observed in lung cancer and breast cancer samples ( 27 , 47 , 48 ). The reason for this contrast may partly be due to the localization of the tumor within the testis.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have shown the feasibility of using long-term archived serum samples for RNA analyses and the variability of the RNA levels (23,31,36). The methods and analyses of the TGCT serum samples were similar to studies by Umu et al (27). The donors have given broad consent for the use of the samples in cancer research.…”
Section: Study Design and Participantsmentioning
confidence: 84%
See 1 more Smart Citation
“…We restricted our selection to cases with at least one sample collected within 10 years prior to cancer diagnosis. The dynamics in RNA levels prior to a cancer diagnosis is sparsely described, however studies in Janus showed that most changes in RNA expression occurred close to a lung cancer diagnosis (8), and depend on staging (9). Based on our knowledge from using pre-diagnostic samples we considered 10 years prior to diagnosis as a reasonable timeframe for the study objectives.…”
Section: Study Design and Sampling Strategymentioning
confidence: 99%
“…Also other factors such as smoking influenced the miRNA expression significantly 18 . Furthermore, we previously also provided first and preliminary indications for pre-diagnostic miRNA profiles 19 in serum of individuals, who were later diagnosed with lung cancer 20 .…”
Section: Introductionmentioning
confidence: 99%